WANPRESTASI PANITIA EVENT JUSTITIA 3X3 BASKETBALL DALAM PERJANJIAN KERJA SAMA PENGADAAN SECARA PESANAN PAKAIAN PANITIA DI TOKO THEMIS KONVEKSI KOTA PONTIANAK - NIM. A1011171194, FITRAH AKBARI (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Implementation of the agreement between the Themis Konveksi Shop business owner and the Justitia 3x3 Baskeball Event committee as the service orderer which in civil law is included in the type of agreement to carry out a sale and purchase. The agreement between the Themis Konveksi Shop business owner and the Justitia 3x3 Baskeball Event committee is made in writing. The agreement gives rise to rights and obligations for the parties, because the agreement meets the requirements for the validity of an agreement as regulated in Article 1320 of the Civil Code, namely the agreement of those who bind themselves, the ability to make or say an agreement, a certain thing and a lawful reasons.This thesis is based on the problem statement: